Chapter 8 Participant-created documents as an elicitation tool Things we might not have otherwise been told - Grant, Aimee (Taylor & Francis, 2018)
Elicitation interviews are where participants are either shown items or asked to bring items to the interview in order to shape the direction of the conversation. This approach is often referred to as being part of 'visual methods'. The chapter focuses in particular on when participants are asked to either bring everyday documents, such as photographs, or when they are asked to create a new document, with both sources serving as a 'topic guide' during interviews, which are directed by the participant. The advantage of this method over many documentary analysis methods is the presence of the author and the ability for the researcher to ask the author questions. This allows us to more easily establish meaning than in participant-absent documentary analysis. A detailed case study is presented of the research that aimed to understand health behaviours, such as smoking and drinking alcohol, during pregnancy. Ten women from deprived areas living on low incomes took part in elicitation interviews. Techniques of elicitation included life-history timelining (drawing a timeline of their life), collaging or using a paper template with thought bubbles to describe what it was like being pregnant, and sandboxing (that is, creating an image or scene using sand and a range of everyday items). Data was analysed using a narrative analysis, which is used to consider change over time. Guidance is provided on how to undertake narrative analysis. The findings highlighted a wide range of barriers and facilitators to abstain from alcohol and smoking during pregnancy, which were related to life circumstances. The key challenges of using such a method, including the ethical implications, are discussed. An exercise with additional data is provided to consolidate learning.